2018
DOI: 10.31403/rpgo.v63i2034
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de sobrepeso y obesidad en el Perú

Abstract: Peru es un país en desarrollo con una prevalencia creciente de enfermedades crónicas no comunicables, entre las que destacan la enfermedad cardiovascular, el cáncer, la diabetes mellitus (DM), el síndrome metabólico (SM) y la obesidad. Objetivo. Revisar los aspectos epidemiológicos de la obesidad y el síndrome metabólico en el Perú en lo concerniente a su prevalencia. Método. Se revisó la literatura a través de una búsqueda sistemática de PubMed, SciELO, LILACS y las publicaciones del Ministerio de Salud, Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 4 publications
2
3
2
8
Order By: Relevance
“…The 2006 National Household Survey carried out in Peru [28] showed that in the age group of 20 to 29 years (7,633 men and 4,265 women), 30.9% of the men were overweight and 8.7% were obese, both lower than in our study. However, in women, the prevalence of overweight and obesity was higher than that reported in this study (30.8% of women were overweight and 10.9% obese).…”
Section: Discussioncontrasting
confidence: 84%
“…The 2006 National Household Survey carried out in Peru [28] showed that in the age group of 20 to 29 years (7,633 men and 4,265 women), 30.9% of the men were overweight and 8.7% were obese, both lower than in our study. However, in women, the prevalence of overweight and obesity was higher than that reported in this study (30.8% of women were overweight and 10.9% obese).…”
Section: Discussioncontrasting
confidence: 84%
“…It is therefore important to control the risk factors for the development of kidney cancer, such as smoking, obesity, hypertension, and chronic kidney disease [ 23 , 24 ]. In fact, the region with the highest mortality rate is the coast, which has the highest prevalence of the aforementioned risk factors [ 10 , 25 , 26 ]. In high income countries the diagnosis, management and treatment of kidney cancer have substantially improved over the last few decades [ 27 ], although with appreciable socio-economic differentials [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2018) (15) (17) , quien observó que en la Encuesta Nacional Demográfica y de Salud Familiar (ENDES), realizada en el 2016, se reportó un IMC promedio de 26,3 en la población total del Perú. En el 2019, la ENDES actualizó este valor, y señaló un ligero aumento en el IMC a 27,0.…”
Section: Discussionunclassified